IDENTITY MANAGEMENT ONLINE AND OFFLINE AMONG MULTI-RELIGIOUS COMMUNITIES - Ichsan, Muhammad Nur; Utari, Prahastiwi; Satyawan, Ign Agung (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2020)
As a multicultural nation Indonesia has various numbers of ethnicity, language, culture and religion. The diversity sometimes cause dynamics in social life including horizontal conflict which one of the reasons behind it is the difference of identity in terms of religion. Religion issue becomes one sensitive issue for plural society which potentially create ?disunity? both in online and the offline spheres. That issue is not separated from the convenience of using social media. The purpose of this research is to portray the reality that really occurs in online and offline spaces related to identity management in multi-religious interaction. What was meant by online space is related to social media literacy, namely observing the dynamics of interaction on religious issues. Whereas in the offline space, this research illustrates the interactions that occur in the management of multi-religious identity in the community of Wiloso hamlet, Girikarto Village, Panggang District, Gunungkidul Regency, Yogyakarta. This research is qualitative with the phenomenology approach, the theory that was used is the identity management theory. The data collection was carried out through observation and in-depth interviews also study of various literature. The result of the research shows that social media has the connection to the emergence of conflict regarding differences in religious identity, especially on political momentum. Whereas in the offline sphere religious harmony can be established because the differences are not seen as differences but are interpreted as wealth in a plural nation.